Global burden of peripheral arterial disease (1990–2021), global burden trends and the impact of blood lead on peripheral arterial disease: a multidimensional analysis based on NHANES, GBD, and Mendelian randomization - Congzhi Yan; Jiahao Chen; Xinbing Xu; Hua Wei; Jinjiao Li (Journal of Translational Medicine)
Abstract Objective Peripheral arterial disease (PAD) is a common cardiovascular disease that it is an important reason for the decline of patients’ quality of life and the increase of family economic burden. To systematically evaluate the association between environmental lead exposure and peripheral arterial disease (PAD) and to characterize the global distribution of PAD disease burden, while exploring differences among regions with varying socioeconomic development. Methods Using data from the National Health and Nutrition Examination Survey (NHANES), the Global Burden of Disease (GBD) database, and genome-wide association studies (GWAS), we employed multivariable logistic regression to examine the link between lead exposure and PAD. Mendelian randomization (MR) was used to infer causality, and we analyzed PAD disease burden trends across countries of differing income levels. Results The burden on PAD patients worldwide shows a downward trend. In high SDI and high middle SDI countries, the burden of PAD gradually decreases, while in low middle SDI and low SDI countries, the burden of PAD gradually decreases. After adjusting for potential confounders, a significant dose-response relationship was observed between blood lead levels and PAD risk (OR = 1.04, 95% CI: 1.00-1.09). This association was more pronounced among males (OR = 1.07, 95% CI: 1.05–1.09), individuals with higher education (OR = 1.24, 95% CI: 1.16–1.32), and patients with hypertension (OR = 1.07, 95% CI: 1.05–1.09). MR analysis supported a causal link between lead exposure and PAD. Global trend analysis indicated that PAD burden is declining in high-income countries but rising in low-income regions, highlighting significant health inequities. Conclusion Environmental lead exposure is significantly associated with increased PAD risk, with notable differences in population susceptibility. These findings underscore the necessity of environmental exposure control and tailored prevention strategies to enhance cardiovascular health worldwide.